A play-based intervention for children with ADHD: A pilot study - Wilkes, S.; Cordier, Reinie; Bundy, A.; Docking, K.; Munro, N. (Wiley-Blackwell Publishing Asia, 2011)
Introduction: Many children with attention deficit hyperactivity disorder (ADHD) have serious social and peer difficulties that can lead to adverse outcomes in adolescence and adulthood. To date, psychosocial treatments have produced poor outcomes in reducing social impairments commonly associated with ADHD. This study aimed to examine the efficacy of a new intervention designed to improve the play and social skills of children with ADHD and their playmates within the natural context of play. Methods: Participants included children (aged 5-11 years) diagnosed with ADHD, age-matched typically developing playmates (n=14/group) and parents of children with ADHD. The intervention involved seven weekly video-recorded free-play sessions; video feed-forward/feedback and therapist- and peer-modelling were used to promote social play. The Test of Playfulness was used as a pre-/post-test measure. Data were subjected to Rasch analysis to calculate measure scores on interval level; dependant sample t-test and Cohen-d calculations were used to measure effect. Results: A dependant samples t-test revealed that both children with ADHD (t=8.1; d.f.=13; P<0.01) and their playmates (t=6.9; d.f.=13; P<0.01) improved in their social play. Results demonstrated a large effect in improving the social play of children with ADHD (d=1.5) and their playmates (d=1.3). Discussion: Results support the use of play, video feed-forward/feedback techniques, therapist- and peer-modelling and parent involvement as an effective means to develop the social play skills of children with ADHD. Further larger-scale research is required.